Failure of Ca(2+)-activated, CREB-dependent transcription in astrocytes - Murray, Peter D. (2009)
Astrocytes participate in signaling via Ca(2+) transients that spread from cell to cell across a multicellular syncytium. The effect, if any, of these Ca(2+) waves on the transcription of CREB-dependent genes is not known. We report here that, unlike neurons, increasing intracellular Ca(2+) in cultured mouse cortical astrocytes failed to activate CREB-dependent transcription, even though CREB was phosphorylated at serine 133. In contrast, both CREB phosphorylation and CREB-dependent transcription were robustly stimulated by increasing cAMP. The failure of Ca(2+)-activated transcription in astrocytes was correlated with the absence of CaMKIV, a Ca(2+)-dependent protein kinase required for Ca(2+)-stimulated gene transcription in neurons. The inability of Ca(2+) to signal via CaMKIV may insulate CREB-dependent gene transcription in astrocytes from activation by Ca(2+) waves.